Interrogating PP1 activity in the MAPK pathway with optimized PP1-disrupting peptides - Wang, Yansong; Hoermann, Bernhard (ChemBioChem, 2019)
Protein phosphatase-1 (PP1)-disrupting peptides (PDPs) are selective chemical modulators of PP1 that liberate the active PP1 catalytic subunit from regulatory proteins; thus allowing the dephosphorylation of nearby substrates. We have optimized the original cell-active PDP3 for enhanced stability, and obtained insights into the chemical requirements for stabilizing this 23-mer peptide for cellular applications. The optimized PDP-Nal was used to dissect the involvement of PP1 in the MAPK signaling cascade. Specifically, we have demonstrated that, in human osteosarcoma (U2OS) cells, phosphoMEK1/2 is a direct substrate of PP1, whereas dephosphorylation of phosphoERK1/2 is indirect and likely mediated through enhanced tyrosine phosphatase activity after PDP-mediated PP1 activation. Thus, as liberators of PP1 activity, PDPs represent a valuable tool for identifying the substrates of PP1 and understanding its role in diverse signaling cascades.
First published: 19 October 2018
Gesehen am 19.06.2019